2018
DOI: 10.1177/2158244018768677
|View full text |Cite
|
Sign up to set email alerts
|

Medical Pluralism and the State: Regulatory Language Requirements for Traditional Acupuncturists in English-Dominant Diaspora Jurisdictions

Abstract: Regulation of traditional acupuncturists has proven controversial in several jurisdictions. In this work, we detail and analyze the range of English-language registration, practice, and record-keeping requirements for regulated traditional acupuncturists across Canada, the United States, and Australia. Drawing on the results of an extensive documentary review and 28 qualitative interviews, we identify five primary themes underpinning policy-related discourses and debate: patient safety; standardized, integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(63 reference statements)
0
4
0
1
Order By: Relevance
“…Where such schemes are in operation, studies suggests that this regulatory model works just as well as for other health occupations (260,288). A similar range of research concerns was found, such as the content of accreditation standards (306,307), implementing evidence-based national examinations (20,(308)(309)(310), regulatory strengthening (311,312), and regulating scopes of practice (294,301,(313)(314)(315)(316). Studies note some of the policy challenges and adjustments required when applying statutory registration to the T&CM occupations, such as evaluating risk, protecting traditional knowledge, applying exible language requirements, or delivering care to underserved populations (288,294,313-315,317-323).…”
Section: Regulation Of Traditional and Complementary Medicine Practit...mentioning
confidence: 70%
“…Where such schemes are in operation, studies suggests that this regulatory model works just as well as for other health occupations (260,288). A similar range of research concerns was found, such as the content of accreditation standards (306,307), implementing evidence-based national examinations (20,(308)(309)(310), regulatory strengthening (311,312), and regulating scopes of practice (294,301,(313)(314)(315)(316). Studies note some of the policy challenges and adjustments required when applying statutory registration to the T&CM occupations, such as evaluating risk, protecting traditional knowledge, applying exible language requirements, or delivering care to underserved populations (288,294,313-315,317-323).…”
Section: Regulation Of Traditional and Complementary Medicine Practit...mentioning
confidence: 70%
“…In a cross-jurisdictional analysis published elsewhere (Ijaz and Boon 2018), we have argued that English-only professional entry requirements for traditional acupuncture practitioners regulated in English-dominant jurisdictions (such as Canada, the United States, and Australia) cannot be justified on the basis of patient safety alone. We do not intend here to reiterate the range of multilingual policy alternatives that may in such contexts effectively address safety as well as considerations related to interprofessional collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, a transitional regulatory council was formed in Ontario with a mandate “to develop the regulations, standards of practices, policies and guidelines” that would ultimately govern the province's TCM practitioners (Transitional Council of the College of Traditional Chinese Medicine Practitioners and Acupuncturists of Ontario [TC‐CTCMPAO] , 1). From the outset, the transitional council took a bilingual (i.e., Chinese and English) approach to communicating in print with prospective members, although public meetings were conducted exclusively in English.…”
Section: An Interpretive Policy Narrativementioning
confidence: 99%
“…Several scholars, critiquing the integrative medicine project, have however suggested a potential for the distinct paradigmatic features of and practices with origins in nonbiomedical therapeutic systems to be co-opted, appropriated, or assimilated in such a process. 65 Model validity, as a theoretical construct, represents a commitment to actively preserving these paradigms and practices in their own right, an approach aligned with the concept of a clearly “articulated,” 66 equitable medical pluralism, 67 rather than an assimilative mode of integration. 65…”
Section: Theorymentioning
confidence: 99%